2022
DOI: 10.1155/2022/6404837
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Evaluation of Knowledge, Attitude, and Practice of Health Practitioners towards Fertility Preservation in Cancer Patients in an Environmental Region of Saudi Arabia

Abstract: Background. Cancer patients face multiple challenges, such as infertility caused by exposure to gonadotoxic agents and gonadal irradiation during cancer treatment. Little is known about the health practitioners’ knowledge and practice regarding fertility preservation and its available options in Saudi Arabia. Thus, this study is designed to evaluate the level of knowledge, attitude, and practice (KAP) towards fertility preservation in cancer patients among health practitioners in an environmental region in Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A study of oncologists reported that only 61% discussed the risk of infertility caused by oncologic treatments, while 45% did not routinely refer the patients to a reproductive medicine specialist [ 16 ]. Although the referral rate has increased, it still has not reached the required level [ 17 20 ]. We found that only two-thirds of the patients were referred to counseling by a gynecologist.…”
Section: Discussionmentioning
confidence: 99%
“…A study of oncologists reported that only 61% discussed the risk of infertility caused by oncologic treatments, while 45% did not routinely refer the patients to a reproductive medicine specialist [ 16 ]. Although the referral rate has increased, it still has not reached the required level [ 17 20 ]. We found that only two-thirds of the patients were referred to counseling by a gynecologist.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Saudi Arabia aimed to assess the attitude of health practitioners towards fertility preservation and showed that clinical practitioners' knowledge is still inadequate. They concluded that there is a need to train health practitioners and establish practice guidelines and fertility preservation clinics for cancer patients [7].…”
Section: The Kap Among Health Practitionersmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%